2012
DOI: 10.1007/s11743-012-1350-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Properties of New Lauryl Amidopropyl Trimethyl Ammoniums

Abstract: A new lauryl amidopropyl trimethyl ammonium methyl carbonate with the formula CH3(CH2)10CONH(CH2)3N+(CH3)3CH3CO3− was synthesized via a high pressure process with tertiary amines and dimethyl carbonate, and its chemical structure was confirmed using 1H‐NMR spectra, mass spectral fragmentation, and FTIR spectroscopic analysis. In addition, several quaternary ammonium salts with new counterions X− (X−=HCO3−, HCOO−, CH3COO−, CH3CH(OH)COO−) were also synthesized by the ion exchange reaction of methyl carbonate qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The plots of the surface tension (c) vs the molar concentration on the natural logarithmic scale (lnC) for the salts at 25°C are shown in Figs. 3, 4 [17], cetyltrimethylammonium [18], 1-dodecylammonium [19], decyltrimethylammonium [20] and other type surfactants [21][22][23]. Table 2 indicates that the counterions are important for maximum values of surface excess concentration-C max , as well as the minimal surface area per molecule of surfactant-A min at the border of aqueous solution with air.…”
Section: Colloidal-chemical Parameters Of the Synthesized Ionic Surfamentioning
confidence: 99%
“…The plots of the surface tension (c) vs the molar concentration on the natural logarithmic scale (lnC) for the salts at 25°C are shown in Figs. 3, 4 [17], cetyltrimethylammonium [18], 1-dodecylammonium [19], decyltrimethylammonium [20] and other type surfactants [21][22][23]. Table 2 indicates that the counterions are important for maximum values of surface excess concentration-C max , as well as the minimal surface area per molecule of surfactant-A min at the border of aqueous solution with air.…”
Section: Colloidal-chemical Parameters Of the Synthesized Ionic Surfamentioning
confidence: 99%
“…Synthesis of 10-UDA Amidopropyl Amine Oxide (10-UDAAO) N-oxide derivative was prepared by stirring a cold solution of N-[3-(dimethylamino) propyl]undec-10-enamide (1a, 5 g, 0.0186 m) in 200 ml of acetone in a 250-ml round-bottomed flask kept in an ice bath. In this stirred solution, 30 % aqueous H 2 O 2 (0.061 m) solution was added drop by drop over a period of 30 min [18]. After completion of the addition, the reaction mixture was allowed to come to room temperature and stirred for 24 h. Progress of the reaction was monitored by TLC.…”
Section: Synthesis Of 10-uda Amidopropyl Betaine (10-udaab)mentioning
confidence: 99%
“…All these surfactants are designed to have an amide moiety in the hydrophobic part in order to increase their biodegradability [17,18]. All these surfactants are designed to have an amide moiety in the hydrophobic part in order to increase their biodegradability [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the development of compounds that are environmentally friendly and biodegradable has gained much attention (Lim et al 2012). Furthermore, it has been reported that the water-solubility and biodegradability of compounds could be improved by adding new polar groups, such as ethers, esters, and amides, into the molecular structure (Liu et al 2012a).…”
Section: Introductionmentioning
confidence: 99%